Injectable Modular Cellularized Blocks via Dual‐Photocrosslinking for Enhanced Cell Therapy - Jiajia Wang; Junyi Wang; Shuhan Duan; Huijing Ma; Wentao Jiang; Rongpu Liu; Huijiao Yan; Licheng Wan; Shaoyi Wang; Rong Yang; Wenjie Zhang (Advanced Healthcare Materials, 2026)
ABSTRACT Cell‐based regenerative medicine is limited by poor survival of transplanted cells and the lack of scalable, ready‐to‐use delivery platforms. Here, we developed an injectable dual‐photocrosslinking microsphere (DP‐MS) bioink composed of Ru/SPS, o‐nitrobenzyl‐modified hyaluronic acid (HANB), and gelatin methacryloyl (GelMA). Orthogonal green (525 nm) and UV (365 nm) light enable sequential crosslinking: first to generate cell‐laden microspheres, and the second step requires only 10 s to induce inter‐microsphere imine bonding without external adhesives. The dual‐photocrosslinking strategy preserved inter‐microsphere spaces, facilitated rapid vascular ingrowth, and enhanced cell survival. In a subcutaneous implantation model, vascular volume in the DP‐MS group was approximately 7‐fold greater than that of constructs lacking inter‐microsphere voids; furthermore, encapsulated stem cells maintained persistent viability over 14 days. Importantly, this superior performance translated into significantly accelerated bone regeneration in a rat mandibular defect model. This platform thus provides a versatile and scalable strategy for developing cellularized products with clinical translation potential.